Temporal Discrimination Thresholds and Proprioceptive Performance: Impact of Age and Nerve Conduction - Odorfer, Thorsten M.; Wind, Teresa; Zeller, Daniel (Frontiers in Neuroscience, 2019)
Background: Increasing attention is payed to the contribution of somatosensory processing in motor control. In particular, temporal somatosensory discrimination has been found to be altered differentially in common movement disorders. To date, there have only been speculations as to how impaired temporal discrimination and clinical motor signs may relate to each other. Prior to disentangling this relationship, potential confounders of temporal discrimination, in particular age and peripheral nerve conduction, should be assessed, and a quantifiable measure of proprioceptive performance should be established. Objective: To assess the influence of age and polyneuropathy (PNP) on somatosensory temporal discrimination threshold (STDT), temporal movement discrimination threshold (TDMT), and behavioural measures of proprioception of upper and lower limbs. Methods: STDT and TDMT were assessed in 79 subjects (54 healthy, 25 with PNP; age 30 to 79 years). STDT was tested with surface electrodes over the thenar or dorsal foot region. TDMT was probed with needle electrodes in flexor carpi radialis and tibialis anterior muscle. Goniometer-based devices were used to assess limb proprioception during (i) active pointing to LED markers, (ii) active movements in response to variable visual cues, and (iii) estimation of limb position following passive movements. Pointing (or estimation) error was taken as a measure of proprioceptive performance. Results: In healthy subjects, higher age was associated with higher STDT and TDMT at upper and lower extremities, while age did not correlate with proprioceptive performance. Patients with PNP showed higher STDT and TDMT values and decreased proprioceptive performance in active pointing tasks compared to matched healthy subjects. As an additional finding, there was a significant correlation between performance in active pointing tasks and temporal discrimination thresholds. Conclusions: Given their notable impact on measures of temporal discrimination, age and peripheral nerve conduction need to be accounted for if STDT and TDMT are applied in patients with movement disorders. Under the caveat of a side observation, the correlation between measures of proprioception and temporal discrimination may prompt further studies on the presumptive link between these two domains.